The Acceleration of Digital Transformation in the Ministry of Finance: What Are the Driven Factors? - Ganjar Asdi Sudrajat (Iapa Proceedings Conference, 2021)
The development of technology, communication, and information has had a major impact and has also changed people's perceptions of public services. People want public services that are fast, transparent, accountable, and accessible. Digital transformation is an effort made by the government to meet people's expectations for public services. The Ministry of Finance is one of the institutions that has been able to implement digital transformation programs in the public sector. The digital transformation program carried out allows the Ministry of Finance to quickly adapt to new habits at work during the Covid-19 pandemic to maintain the continuity of the organization's tasks. This study aims to determine the various factors that support the implementation of the digital transformation program at the Ministry of Finance. The study used a descriptive method with a qualitative approach. The data was obtained through a literature study by examining various literatures related to the Ministry of Finance's digital transformation program. The results of the study show that the digital transformation program at the Ministry of Finance is strongly supported by the commitment and full support of the leader, resources (infrastructure, system, human resources, and regulations), and employee engagement.